Agricultural dust explosions in 2013 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were seven dust explosions reported in the U.S. in 2013 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 10 in 2012 and a ten-year average of 9.9 explosions.
Keywords: Grain dust; Dust explosions